2009
DOI: 10.1161/hypertensionaha.108.127290
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Alters Left Ventricular Geometry and Attenuates Heart Failure in Dahl Salt-Sensitive Hypertensive Rats

Abstract: Abstract-The clinical efficacy of exercise training in individuals with heart failure is well established, but the mechanism underlying such efficacy has remained unclear. An imbalance between cardiac hypertrophy and angiogenesis is implicated in the transition to heart failure. We investigated the effects of exercise training on cardiac pathophysiology in hypertensive rats. Dahl salt-sensitive rats fed a high-salt diet from 6 weeks of age were assigned to sedentary or exercise (swimming)-trained groups at 9 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 43 publications
4
48
0
1
Order By: Relevance
“…A recent study in hypertensive rats indicated that exercise training attenuated the development of heart failure and also increased survival and attenuated LV concentricity without a reduction in LV mass. 39 Similar to these findings, RWT in our fit older group was thinner than in the unfit group, without a reduction in the LV mass. These results suggest that exercise has a direct beneficial effect on LV concentric remodelling.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study in hypertensive rats indicated that exercise training attenuated the development of heart failure and also increased survival and attenuated LV concentricity without a reduction in LV mass. 39 Similar to these findings, RWT in our fit older group was thinner than in the unfit group, without a reduction in the LV mass. These results suggest that exercise has a direct beneficial effect on LV concentric remodelling.…”
Section: Discussionsupporting
confidence: 87%
“…21,22 For evaluation of macrophage infiltration into the LV myocardium, tissue sections were subjected to immunostaining for the monocyte-macrophage marker CD68, as described previously. 23 Details are available in the online-only Data Supplement.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…16,17 To evaluate macrophage infiltration into the myocardium, we performed immunostaining for the monocyte-macrophage marker CD68 with frozen sections (thickness, 5 mm) that had been fixed with acetone. Endogenous peroxidase activity was blocked by exposure of the sections to methanol containing 0.3% hydrogen peroxide.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%